The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14081915
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Strength of Circular Tube Open Wagons with Aluminum Foam Filled Center Sills

Abstract: The study deals with an application of aluminum foam as an energy-absorbing material for the carrying structure of a rail car. The material is particularly recommended for circular tube carrying structures. The authors conducted mathematical modeling of dynamic loads on the carrying structure of an open wagon that faces shunting impacts with consideration of the center sill filled with aluminum foam. It was established that the maximum accelerations on the carrying structure of an open wagon were 35.7 m/s2, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…1921 The experimental results show that the crushing behavior of foam-filled mixed structure is obviously improved comparing with that of empty hybrid structure, and the crushing resistant behavior of foam-filled hybrid tubes is positively related to the situation of the adding material. 2224 The results also revealed that the peak force is improved by using the aluminum alloy foam inside the composites. 25,26 During an impact accident, the thin-walled structures in the automobile may play a key role in protecting passengers, and thus a lot of research has been done on foam filling materials.…”
Section: Introductionmentioning
confidence: 87%
“…1921 The experimental results show that the crushing behavior of foam-filled mixed structure is obviously improved comparing with that of empty hybrid structure, and the crushing resistant behavior of foam-filled hybrid tubes is positively related to the situation of the adding material. 2224 The results also revealed that the peak force is improved by using the aluminum alloy foam inside the composites. 25,26 During an impact accident, the thin-walled structures in the automobile may play a key role in protecting passengers, and thus a lot of research has been done on foam filling materials.…”
Section: Introductionmentioning
confidence: 87%
“…Similar trends can be seen in the railway transportation and construction industries. For example, the development of "aluminum" light passenger carriages increases train movement on the railway line by up to two times [7,8]. Furthermore, it is well known that the use of aluminum structures in construction contributes to a significant reduction in the load on the foundation when high-rise buildings and other large-scale structures are built.…”
Section: The Merits and Advantages Of Aluminum And Aluminum-based Alloysmentioning
confidence: 99%
“…The authors of [14,15] make improvements to the load-bearing structures of freight cars to reduce their dynamic load under operational modes. The set goal is achieved by using a material with energy-absorbing properties for the load-bearing structures of freight cars containing round cross-section pipes.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The above review of literary sources [9][10][11][12][13][14][15][16][17][18] allows us to conclude that the issue related to reducing the load on the bearing structure of a covered freight car under operational load modes requires further research and development.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%